KEABSAHAN TANDA TANGAN ELEKTRONIK DALAM PEMBUKTIAN HUKUM ACARA PERDATA INDONESIA - Hudzaifah, Husnul (Katalogis, 2015)
The use of electronic documents signed with electronic signatures as evidence different from the evidence set in the Civil Code, because the level of originality or authenticity still need to be proven in advance, or in other words to have some reservations to the electronic evidence has the force of law, This study aims to determine the validity of electronic signatures in the proof of Indonesian civil procedure law, as well as to determine the civil dispute resolution efforts towards electronic document signed by electronic signature. Writing this using normative legal research, making use of existing legal library materials and the linkage with the issues to be investigated. The conclusions of this research is said to be valid electronic signature when using electronic systems in accordance with the applicable legislation, namely the Law on Information and Electronic Transactions Article 16 Paragraph (1), the expert testimony is also one of the elements that are considered essential for the process examination because it provides an explanation regarding the authenticity or the authenticity of the evidence that an electronic signature submitted.